Mode-Locking Thulium-Doped Fiber Laser With 1.78-GHz Repetition Rate Based on Combination of Nonlinear Polarization Rotation and Semiconductor Saturable Absorber Mirror - Jia Qingsong; Wang Tianshu; Ma Wanzhuo; Wang Zhen; Su Qingchao; Bo Baoxue; Jiang Huilin (IEEE Photonics Journal, 2017)
We experimentally demonstrate a passively mode-locking thulium-doped fiber laser based on the combination of the nonlinear polarization rotation (NPR) and the semiconductor saturable absorber mirror (SESAM). In contrast to SESAM mode-locking merely, the fiber lasers based on NPR working together with SESAM have more advantages. By using two mode-locking mechanisms, the nonlinear effect can be enhanced tremendously; then, the threshold of high-order harmonic mode-locking (HML) pulse trains can be decreased, and the pulses width can be compressed. The shapes of the pulses can also be reshaped better, and the HML pulse trains stability can be improved. The high repetition rate of 1.78 GHz is obtained by both NPR and SESAM in the experiment. Because of the variation of the gain-and-loss distribution in the cavity, the output wavelength of mode-locking fiber laser can be tuned from 1839 to 1890 nm, and the multiwavelength HML is also observed in the experiment.